PENGUATAN KAPASITAS GURU BERBASIS MANAJEMEN PEMBELAJARAN - Beatrix Tomasila; Sarlota Singerin (Universitas Pattimura, 2023)
Learning is a very important activity in education. Teachers must also understand and master the knowledge of learning management both inside and outside the classroom. Teachers must be able to choose and apply learning methods based on the complexity of the material and the personality of each student. This will be realized if teachers, as learning designers, have learning management competencies. The teachers at SD Negeri 6 Dobo are not yet able to manage learning effectively and efficiently. The existing teachers still have many deficiencies in teaching competencies, the implication of which is that active, innovative, creative, effective, and enjoyable learning activities have not been realized. In connection with the description above, the teacher capacity strengthening program based on learning management established as a Community Service Program of the Education Administration Study Program, Faculty of Education and Teaching Sciences, Pattimura University is an effort to produce strong teachers in realizing the expected student quality of being active, innovative, creative, effective, and enjoyable in the learning process